2003
DOI: 10.1039/b303252c
|View full text |Cite
|
Sign up to set email alerts
|

Aziridinyl anions from a chiral, nonracemic 2-isopropylidineaziridine: surprisingly diastereoselective alkylation reactions

Abstract: Lithiation and alkylation of a 2-isopropylidineaziridine bearing an (S)-alpha-methylbenzyl group on nitrogen proceeds with high levels of diastereocontrol (80-90% de).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…We used geometrically pure ( Z )‐ and ( E )‐ N ‐benzyl‐2‐ethyleneaziridine,5d to produce ( Z )‐ 11 (59 %) and ( E )‐ 11 (71 %), respectively, by lithiation and reaction with 13 . Finally, deprotonation and diastereocontrolled alkylation of ( S )‐ N ‐(1‐phenylethyl)‐2‐isopropylidineaziridine gave 12 (63 %) as a single diastereomer whose relative configuration was assigned by correlation with literature data 5c…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…We used geometrically pure ( Z )‐ and ( E )‐ N ‐benzyl‐2‐ethyleneaziridine,5d to produce ( Z )‐ 11 (59 %) and ( E )‐ 11 (71 %), respectively, by lithiation and reaction with 13 . Finally, deprotonation and diastereocontrolled alkylation of ( S )‐ N ‐(1‐phenylethyl)‐2‐isopropylidineaziridine gave 12 (63 %) as a single diastereomer whose relative configuration was assigned by correlation with literature data 5c…”
Section: Methodsmentioning
confidence: 80%
“…As part of a program aimed at exploring the scope and utility of 2‐methyleneaziridines 1 in organic synthesis,5 we realised that these heterocycles might serve as alternative precursors to 2‐aminoallyl cations. As methyleneaziridines can be functionalised readily at C3,5c we felt that this methodology might be especially useful for the development of intramolecular [4+3] cycloadditions. The general strategy is depicted in Scheme .…”
Section: Methodsmentioning
confidence: 99%
“…Gratifyingly, high levels of asymmetric induction have been achieved when isopropylidineaziridine (S)-29 was lithiated and alkylated by a range of electrophiles, including MeI, PhCH 2 Br, CH 2 ] CHCH 2 Br, Ph 2 CO and Me 3 SiCl (Scheme 9). 22 Shipman and Luisi et al further investigated the stereoselectivity observed in the lithiation-alkylation of MAs. 23 Factors such as nitrogen inversion barrier, the stereochemistry at the nitrogen atom, the substitution pattern of the MAs, and the reaction conditions were all taken into consideration.…”
Section: Functionalization Of Monocyclic Masmentioning
confidence: 99%
“…Sulfonylaziridine 243 was halogenated in carbon tetrahalides in the presence of KOH as base [86] Enantiopure methyleneaziridine 248 could be lithiated and subsequently trapped with a variety of electrophiles in a highly diastereoselective manner (Scheme 5.63) [89]. …”
Section: Metalated Aziridinesmentioning
confidence: 99%